2014
DOI: 10.4028/www.scientific.net/amm.556-562.1143
|View full text |Cite
|
Sign up to set email alerts
|

Research Status and Development Trend of Vane Pump

Abstract: The classification, working principle and structure characteristic of vane pump was introduced. Combined with the research and development status of vane pump at home and abroad. It Main, introduced the single-acting vane pump and the working principle of double-acting vane pump, its development trend was summarized, which promote the development of vane pump technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Wang et al found effective measures to control gear pump noise and relieve trapped oil when analyzing external gear pump vibration and evaluating pump body design optimization [13]. When a blade pump is functioning, it has high requirements regarding the pressure on both sides of the blade and faces the problems of a short working life and small flow [14]. The rotating speed range of a blade pump is rigorous, and the cleaning degree of the fluid has a high requirement, so the blade pump is at a disadvantage in its scope of application [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al found effective measures to control gear pump noise and relieve trapped oil when analyzing external gear pump vibration and evaluating pump body design optimization [13]. When a blade pump is functioning, it has high requirements regarding the pressure on both sides of the blade and faces the problems of a short working life and small flow [14]. The rotating speed range of a blade pump is rigorous, and the cleaning degree of the fluid has a high requirement, so the blade pump is at a disadvantage in its scope of application [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A volumetric pump sucks and discharges the liquid by periodically increasing and decreasing the working volume due to the movement of functional parts [4]. A dynamic pump is driven by vanes that rotate the liquid at high speed and transfer mechanical energy to the conveyed liquid [5]. In an electromagnetic pump, an energized fluid in a magnetic field flows in a specific direction under the action of electromagnetic force.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Radar stealth technology refers to the weakening of signals from an object and reducing the probability of being discovered, in order to conceal and protect the target [1]. Voice stealth technology, radar stealth technology, visible light stealth technology, and infrared stealth technology are the main stealth technologies currently in use, among which radar stealth technology is considered to be the most important [2].…”
Section: Introductionmentioning
confidence: 99%